PENGARUH KEPEMIMPINAN, KOMPETENSI DAN SARANA PRASARANA TERHADAP KINERJA PEGAWAI KELURAHAN TANAH GROGOT KECAMATAN TANAH GROGOT KABUPATEN PASER - Sumiyanto Sumiyanto; Anthonius Junianto Karsudjono (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2026)
The purpose of this research is to determine and analyze the following in Tanah Grogot Village, Tanah Grogot District, Paser Regency: 1) The significant influence of leadership, competence, and infrastructure simultaneously on employee performance. 2) The significant influence of leadership, competence, and infrastructure partially on employee performance. 3) Variables that have a dominant influence on employee performance.This research is quantitative. The population was 32 employees of Tanah Grogot Village, Tanah Grogot District, Paser Regency. The sample size was 31 employees who left their leadership positions. The sampling technique used was purposive sampling. The analysis model used was multiple linear regression analysis.The results of the study found that: 1) Leadership, Competence and Infrastructure simultaneously influence the performance of employees in Tanah Grogot Village, Tanah Grogor District, Paser Regency. 2) Leadership, Competence and Infrastructure partially influence the performance of employees in Tanah Grogot Village, Tanah Grogor District, Paser Regency. 3) Leadership dominantly influences the performance of employees in Tanah Grogot Village, Tanah Grogor District, Paser Regency